2015
DOI: 10.1002/smll.201500562
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Heterogeneity of the Molecular Structure of Individual hIAPP Amyloid Fibrils Revealed with Tip‐Enhanced Raman Spectroscopy

Abstract: Type 2 diabetes mellitus is characterized by the pathological deposition of fibrillized protein, known as amyloids. It is thought that oligomers and/or amyloid fibrils formed from human islet amyloid polypeptide (hIAPP or amylin) cause cell death by membrane damage. The molecular structure of hIAPP amyloid fibrils is dominated by β-sheet structure, as probed with conventional infrared and Raman vibrational spectroscopy. However, with these techniques it is not possible to distinguish between the core and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
79
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 65 publications
(102 reference statements)
13
79
0
Order By: Relevance
“…In contrast to ROA and CD, TERS exclusively probes the surface of a sample enabling a differentiation of core and surface composition of proteins, as has been demonstrated for amyloid fibrils. 17,18 …”
mentioning
confidence: 99%
“…In contrast to ROA and CD, TERS exclusively probes the surface of a sample enabling a differentiation of core and surface composition of proteins, as has been demonstrated for amyloid fibrils. 17,18 …”
mentioning
confidence: 99%
“…Another common feature of amyloid fibrils is a highly organized hydrogen bonded β-sheet structure core, which is detectable in the bulk sample with various techniques, including solid-state nuclear magnetic resonance (NMR)2, X-ray diffraction2, vibrational circular dichroism12, infrared spectroscopy13, and Raman spectroscopy1415. Single-particle studies on the nanoscale with tip-enhanced Raman scattering (TERS) on insulin fibrils161718 and human islet amyloid precursor peptide (hIAPP) fibrils19 revealed that the surface is not only composed of β-sheet structures but also has a high propensity for α-helix/unordered structures. Whereas conventional Raman spectroscopy is highly specific but limited to bulk samples, the intrinsic high sensitivity of TERS not only provides access to single amyloid fibrils but also allows the distinction between amino acids and conformations on fibril surfaces.…”
mentioning
confidence: 99%
“…Figure a,b reports a collection of selected TERS spectra acquired from type A and type B oligomer samples. In spite of the local signal variations that are consequential to the chemical complexity produced by adjacent amino acid residues, a tentative assignment of the main TERS bands was made based on the Raman spectra (see Table ). In particular, aromatic ring vibrations are visible at 1003 and 1027 cm −1 (Phe) and within the 1550–1620 cm −1 range (Trp, Tyr, Phe) .…”
Section: Resultsmentioning
confidence: 99%